Integrating cultural heritage and values through expressive arts in the school curriculum for personality development - Ayob, Salmah (UUM College of Arts and Sciences, 2004)
This article is an attempt to heighten the awareness of the general readers, educators as well as professional practitioners to recognize the importance of cultural heritage and values and their contributions to personality development of young children. Children are not born with culture, but rather learn it through enculturation and socialization. Multicultural education is viewed as an intervention and an on-going assessment process to help institutions and individuals become more responsive to the human condition, individual cultural heritage, values and integrity, and cultural pluralism in society. It addresses the aesthetic development of young children, especially in the areas of creativity in music, creative movement, dance, creative dramatics, arts and literature which are proudly acclaimed as parts of our cultural heritage. It focuses to define what is meant by aesthetics and creativity. It further discusses the significant values of our cultural heritage in relation to aesthetic and creative development as well as personality development of the young ones.